2008
DOI: 10.1590/s0103-17592008000400004
|View full text |Cite
|
Sign up to set email alerts
|

A fault detection and isolation system for cooperative manipulators

Abstract: The problem of fault detection and isolation (FDI) in cooperative manipulators is addressed in this paper. Four FDI procedures are developed to deal with free-swinging joint faults, locked joint faults, incorrectly measured joint position, and incorrectly measured joint velocity. Free-swinging and locked joint faults are isolated via neural networks. For each arm, a Multilayer Perceptron (MLP) is used to reproduce the dynamics of the fault-free robot. The outputs of each MLP are compared to the actual joint ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The previously discussed methods all address the level of subsystem or actuator FDIR. In [27], a Bayesian network was successfully used in order to describe the spatial relationships between the different parts of a 6-DoF robotic manipulator, which was used in order to detect failures such as blocked or deformed joints.…”
Section: [29]mentioning
confidence: 99%
See 1 more Smart Citation
“…The previously discussed methods all address the level of subsystem or actuator FDIR. In [27], a Bayesian network was successfully used in order to describe the spatial relationships between the different parts of a 6-DoF robotic manipulator, which was used in order to detect failures such as blocked or deformed joints.…”
Section: [29]mentioning
confidence: 99%
“…Although there are many different techniques and studies using and evaluating advanced FDIR methods, only the remote agent experiment was actually flown and tested in space, whereas all the other projects remain theoretical simulations including a few specific on ground hardware tests. The projects [27] and [3 1] were applied to manipulators on ground. The proposed principle, however, could be transferred to the space domain.…”
Section: [29]mentioning
confidence: 99%
“…This study deals with the most common used serial, open chained and rigid robot manipulator and only a detailed review on this type of robots is given here. Studies on other type robots can be found in (Goel et al, 2000;Tinós & Terra, 2002). Most studies on FDI for robot manipulators are based on nonlinear observer approaches.…”
Section: Literature Overview Of Model-based Fdi For Nonlinear Systemsmentioning
confidence: 99%
“…Consequently, modelfree FDI approaches have been proposed. In [6], two artificial neural networks were employed in a fault detection and isolation system for cooperative robotic manipulators. This FDI method could be applied to cooperative systems with more robots.…”
Section: Introductionmentioning
confidence: 99%